Bunium persicum (Boiss.) B. Fedtsch: An overview on Phytochemistry, Therapeutic uses and its application in the food industry - Hassan Hassanzadazar, Borzoo Taami, Majid Aminzare, Shahrzad Daneshamooz (Journal of Applied Pharmaceutical Science, 2018)
Bunium persicum (Boiss.) B. Fedtsch as a plant of the Apiaceae family grows in different regions of Asia such as Central Asia, Iran, Pakistan, Afghanistan, and India. This plant has significant medicinal, antimicrobial and antioxidant properties which indicate its high potential for use in the medicine and food industry. In traditional medicine, it is used to treat or improve some cases such as digestive and urinary disorders, diabetes, obesity and increasing breast milk. A comprehensive literature review was conducted by searching studies in all relevant authentic scientific databases. Databases were searched for the terms Bunium persicu, Cuminum cyminum, Black zire, black caraway, Carum carvi, Persian Cumin, Zire kuhi, Shah zira, Kala Zeera, Jira, Wild caraway and wild cumin without limitation up to 10 November 2017. According to researches, this plant and its derivatives are valuable compounds that have antimicrobial, antioxidant, anti-inflammatory, anti-diabetes, antihyperlipid and analgesic properties. Bunium persicum essential oil contains high levels of oxygenated monoterpenes, especially γ-Terpinene, cuminaldehyde, ρ-cymene and limonene, which has high antimicrobial and antioxidant effects. Due to the fact that Bunium persicum is widely used in people’s diet as a flavoring agent, there is no major concern about the toxic effects of this plant.
Keywords: Antimicrobial effect,Antioxidant effect,Bunium persicum,Phytochemistry,Therapeutic effects